The Social Construction of Exclusive Breastfeeding for Working Women in Bengkulu, Indonesia - Herlina, Muria (International Journal of Psychosocial Rehabilitation, 2020)
This study examined exclusive breastfeeding using a social construction assessment to determine the reality of the problems presented by working mothers’ activities, specifically in the context of the low level of exclusive breastfeeding in Indonesia. The research was based on data obtained from 35 women using a questionnaire. In order to obtain more detailed information, we conducted interviews with 10 informants. There is no difference in exclusive breastfeeding based on the women’s level of education and knowledge. Furthermore, the types of occupation, income levels, and age of the respondents were found to present no significant differences. In their social construction, the role of moments of externalization and objectivation were stronger compared to the role of internalization in the family with respect to the practice of exclusive breastfeeding. The family (husbands and parents), government policies, and the workplace played roles that contributed to encouraging women to practice exclusive breastfeeding. It is important for governments to design policies that protect the rights of children and women in order to lower the infant mortality rate in Indonesia.